Valuation of angiogenesis in bovine xenografts implanted in intracorporal sites of rabbits as models of in-vivo bioreactors - Montanhim, G. L. [UNESP]; Silva, M. T.S.; Conceição, M. E.B.A.M.; Rocha, T. S.; Yamashiro, L. M.; Ribeiro, J. O.; Hataka, A. [UNESP]; Moreira, P. R.R.; Minto, B. W. [UNESP]; Dias, L. G.G.G. [UNESP]; Moraes, P. C. [UNESP] (FapUNIFESP (SciELO), 2021)
The aim of this study was to evaluate neovascularization of bovine xenografts implanted in intracorporeal sites of rabbits (bioreactors). 30 rabbits were used, divided into 6 groups, according to the evaluation time (7, 15, 30, 45, and 60 days); each animal received xenogenic implants in 3 different intracorporeal sites (A1- omentum bag; A2 - intermuscular space of quadriceps femoris; A3 - subperiosteal of ilium bone). Histological assessments graded the presence of angiogenesis, the number of inflammatory cells, newly formed bone tissue, and the presence of giant cells. Histological analyses showed intense angiogenesis in all implanted xenografts. Presence of inflammatory infiltrate and giant cells at the A1 implant site and presence of bone neoformation at the A3 implant site were noted. Degeneration of implants and formation of a fibrous capsule were noted. When comparing the interaction of the site with the days of evaluation, statistical analysis showed a significant difference (p≤0.05) in any time of neovascularization analysis. The vascular endothelial growth factor (VEGF) and inflammatory cells of the omentum in its structure, may have contributed to the greater presence of neovessels and inflammatory cells, a fact that may indicate functionality as a possible bone substitute.
Avaliação da angiogênese em xenoenxertos bovinos implantados em sitios intracorpóreos de coelhos como modelos de biorreatores in vivo
Keywords: bone substitute; neovascularization; osteoinduction; xenogeneic graft